SCIENTIFIC CONTENT OF TAX FUNCTIONS - Eshonov M-A.X. (Journals Park Publishing, 2023)
This article analyzes the scientific opinions of a number of authors who expressed their opinions about the functions of the tax category. It is recognized that there is no consensus on the number of tax functions due to the fact that these authors did not pay attention to the existing difference between the role and functions of tax. As a result, it is explained that, like the tax itself, its functions are objective and have only fiscal and regulatory functions.
Keywords: Tax, tax functions, role of tax, tax category, fiscal function of tax, regulatory function of tax.